What do musicians think caused their musculoskeletal symptoms?. Issue 3 (3rd July 2022) - Stanhope, Jessica; Pisaniello, Dino; Weinstein, Philip
Abstract : Objectives. The purpose of this study was to determine the factors that university music students and professional musicians believe caused their musculoskeletal symptoms (MSSs). Methods . Data were collected using a questionnaire distributed to university music students and professional musicians. Using a musician-driven data collection approach, musicians with MSSs were asked to nominate their top three perceived causes of their symptoms. Responses were categorized, and percentages reported for the main categories. Results . Of the 213 musicians, 37.6% reported biological factors, 21.1% reported external, physical factors, 93.9% reported behavioural factors, 18.8% reported psychosocial factors and 9.9% reported 'other' factors (e.g., accidents) as the perceived causes of their MSSs. Conclusion . This study is the first to investigate perceived causes of musicians' MSSs across a diverse range of musicians, using musician-driven methods. By using open response data collection strategies, a comprehensive, unbiased list of perceived causes of MSSs was compiled. Perceived causes not identified in previous research included manual handling, physical activity and sleep problems. Future research should consider the association between perceived causes and MSSs, and barriers and enablers of behaviour changes that may prevent MSSs. This research may guide the development of new strategies to reduce the burden of MSSs in musicians.